2021
DOI: 10.3390/v13040695
|View full text |Cite
|
Sign up to set email alerts
|

When the COVID-19 Pandemic Surges during Influenza Season: Lessons Learnt from the Sentinel Laboratory-Based Surveillance of Influenza-Like Illness in Lombardy during the 2019–2020 Season

Abstract: This paper outlines the role of Lombardy’s regional influenza reference laboratory (Northern Italy) in the surveillance of influenza-like illnesses (ILIs) in monitoring SARS-CoV-2 circulation by analyzing 631 consecutive nasopharyngeal swabs (NPSs) collected from ILI outpatients by sentinel physicians during the 2019–2020 season. The samples were tested by specific real-time RT-PCRs targeting SARS-CoV-2, influenza viruses, and RSVs. Results: Of these NPSs, 31% tested positive for influenza viruses, 10% for SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
4
20
0
Order By: Relevance
“…The increase in the pre-pandemic period could be linked to early diagnosis of MM in people presenting respiratory symptoms in a silent phase of the pandemic. Nevertheless, detailed epidemiological and virology 9 investigations conducted on data from the beginning of the early phases of the pandemic in Italy showed that only a few hundred COVID-19 patients sought care before 20 February 2020, 10 and the seasonal influenza virus was predominant until the end of February 2020. 9 However, the data show some geographical differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the pre-pandemic period could be linked to early diagnosis of MM in people presenting respiratory symptoms in a silent phase of the pandemic. Nevertheless, detailed epidemiological and virology 9 investigations conducted on data from the beginning of the early phases of the pandemic in Italy showed that only a few hundred COVID-19 patients sought care before 20 February 2020, 10 and the seasonal influenza virus was predominant until the end of February 2020. 9 However, the data show some geographical differences.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, detailed epidemiological and virology 9 investigations conducted on data from the beginning of the early phases of the pandemic in Italy showed that only a few hundred COVID-19 patients sought care before 20 February 2020, 10 and the seasonal influenza virus was predominant until the end of February 2020. 9 However, the data show some geographical differences. The patterns of increase and decrease in the number of diagnoses during the different phases of the pandemic do not show any association with regional COVID-19 incidence nor with the physical distancing measures.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies that retrospectively screened respiratory samples collected from patients with influenza-like and respiratory symptoms, including those collected within the framework of influenza surveillance, found no evidence for SARS-CoV-2 (table 2),37–41 including during times when community SARS-CoV-2 transmission in respective populations was already occurring 20. Nonetheless, the combination of all knowledge acquired so far from retrospective studies strongly suggests that SARS-CoV-2 was circulating outside of China considerably earlier than the currently postulated time frame of late December 2019/early January 2020, at least in some parts of the world.…”
Section: Implications Of Available Early Circulation Evidencementioning
confidence: 98%
“…However, a serum antibody test study demonstrated that although approximately 23% of COVID-19 patients had SARS-CoV-2 cross-reactive antibodies during the prepandemic period, these antibodies were not neutralizing antibodies for SARS-CoV-2 and were not related to reducing COVID-19 susceptibility and hospitalization 20 . A cross-sectional study reported different contracting patterns of influenza viruses and SARS-CoV-2 21 . There were no coinfected cases in their study, and SARS-CoV-2 infection was higher in elderly individuals, while influenza virus infection was more prevalent in children less than 5 years old 21 .…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study reported different contracting patterns of influenza viruses and SARS-CoV-2 21 . There were no coinfected cases in their study, and SARS-CoV-2 infection was higher in elderly individuals, while influenza virus infection was more prevalent in children less than 5 years old 21 . Furthermore, the antiinfection effects of nonpharmacologic interventions, such as wearing face masks, social distancing, restrictions on movement and health behaviors of infected patients, could mediate the decreased COVID-19 incidence in patients with influenza/URI 22 24 .…”
Section: Discussionmentioning
confidence: 99%